2013
DOI: 10.1007/s00701-013-1643-y
|View full text |Cite
|
Sign up to set email alerts
|

Sodium fluorescein–guided resection under the YELLOW 560 nm surgical microscope filter in malignant brain tumor surgery—a feasibility study

Abstract: The use of FL for the resection of brain tumors is safe and feasible. Presumably, the visualization of the tumor margin depends on the histopathology and on the pre-treatment status. A randomized evaluation of FL under the YELLOW 560 nm filter is planned to prospectively analyze the extent of resection in patients with malignant brain tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
104
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(110 citation statements)
references
References 28 publications
2
104
0
2
Order By: Relevance
“…This might be related also to the use of specific filters that enable reduction of the total dose of fluorescein injected 1,8,18 with a possible impact on reduction of side effects. Rare adverse events, including anaphylactic reactions, after fluorescein injection have been reported in the ophthalmological and neurosurgical literature, 3,9,10,16,28,33 but no side effects were registered with the use of low-dose fluorescein in more recent pa- pers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be related also to the use of specific filters that enable reduction of the total dose of fluorescein injected 1,8,18 with a possible impact on reduction of side effects. Rare adverse events, including anaphylactic reactions, after fluorescein injection have been reported in the ophthalmological and neurosurgical literature, 3,9,10,16,28,33 but no side effects were registered with the use of low-dose fluorescein in more recent pa- pers.…”
Section: Discussionmentioning
confidence: 99%
“…14 In addition, the feasibility of fluorescein-guided removal of HGGs has been suggested by the results of several studies. 8,18,20 The results of one prospective study suggested a possible improvement of the extent of resection using fluorescein, although in that study surgery was performed without a specific filter integrated into the surgical microscope. 5 In 2011, our group started the first prospective Phase-II trial with the aid of a microscope-integrated fluorescence kit (FLUOGLIO) to evaluate the safety of and obtain initial data about the efficacy of fluorescence-guided resection of HGGs.…”
mentioning
confidence: 99%
“…The emergence of surgical microscopes outfitted with a fluorescein-specific filter has enabled broader application of fluorescein guidance to glioma microsurgery 2,17,26 with a statistically strong association between fluorescein staining and tumor tissue, as well as reports that fluorescein guidance safely facilitates complete resection of contrast-enhancing (CE) tumor. 1,9 However, small study groups have offered limited evidence of the added utility of fluorescein guidance, and rigorous assessment of fluorescein as a marker for tumor pathology in regions beyond MRI contrast enhancement has not been performed.…”
Section: 27mentioning
confidence: 99%
“…20 The use of fluorescein as a tumor marker for resection has been widely investigated for multiple tumor types, including skull base tumors, 6 metastatic brain tumors, 21 and high-grade gliomas. 10,11,16,23,24 Fluorescein has not been previously demonstrated as an agent that bioaccumulates in a glioblastoma flank xenograft model. 10 However, conjugation of fluorescein to albumin demarcates glioblastoma tumors in humans and animal models.…”
mentioning
confidence: 99%